Optimization of Pharmaceutical Supply Chain Resilience in Post-Pandemic Era - Nolbert, Andi; Samuel, Buyako (Journal of Current Research In Multidisciplinary, 2025)
The global pharmaceutical industry has faced unprecedented disruptions due to the COVID-19 pandemic, exposing significant vulnerabilities in traditional supply chain models. This research, titled "Optimization of Pharmaceutical Supply Chain Resilience in the Post-Pandemic Era," investigates strategic frameworks to enhance the agility and robustness of drug distribution networks. The primary objective is to identify critical success factors that allow pharmaceutical companies to maintain a steady supply of essential medicines during volatile periods. The study utilizes a qualitative descriptive methodology, integrating data from global energy and health reports with strategic management theories. Key areas of focus include the transition from "Just-in-Time" to "Just-in-Case" inventory strategies, the role of digital transformation, and the importance of regionalized manufacturing hubs. Findings suggest that resilience is not merely a technical attribute but a strategic capability driven by real-time data visibility and multi-stakeholder collaboration. The research provides a comprehensive roadmap for policymakers and pharmaceutical executives to build a supply chain that is not only efficient but also resilient against future systemic shocks. By adopting the proposed optimization strategies, organizations can ensure patient safety and maintain operational continuity in an increasingly unpredictable global landscape.